Wireless Rechargeable Sensor Network Fault Modeling and Stability Analysis - Mugunthan, S. R. (Journal of Soft Computing Paradigm, 2021)
Wide attention has been acquired by the field of wireless rechargeable sensor networks (WRSNs ) across the globe due to its rapid developments. Addressing the security issues in the WRSNs is a crucial task. The process of reinfection, charging and removal in WRSN is performed with a low-energy infected susceptible epidemic model presented in this paper. A basic reproductive value is attained after which the epidemic equilibrium and disease-free points of global and local stabilities are simulated and analyzed. Relationship between the reproductive value and rate of charging as well as the stability is a unique characteristic exhibited by the proposed model observed from the simulations. The WRSN and malware are built with ideal attack-defense strategies. When the reproductive value is not equal to one, the accumulated cost and non-optimal control group are compared in the sensor node evolution and the optimal strategies are validated and verified.